Programa de terapia assistida por cavalos na funcionalidade e qualidade de vida em pessoas com Epilepsia - Santos, Caroline Souza (2024)
Epilepsy is a clinical condition characterized by an excessive and abnormal disturbance of brain cells, causing epileptic seizures and neurobiological, cognitive and social changes. Equine assisted therapy (CAT) is a therapeutic method that uses horses in an interdisciplinary approach through recreational and sporting activities. This study investigated the impact of TAC on quality of life, functional independence, sleep quality, anticonvulsant medications and frequency of epileptic seizures. Fourteen participants aged between four and thirty-five years, diagnosed with focal epilepsy, participated in a structured TAC program. The program consisted of 36 sessions, each session lasting 30 minutes and held weekly. Data collection occurred at four different moments: baseline (T1), after 12 sessions (T2), after 24 sessions (T3) and after 36 sessions (T4). Assessments included Quality of Life in Epilepsy (QOLIE-31), Functional Independence Measure (MIF), Pittsburgh Sleep Quality Index (PSQI), and Liverpool Adverse Event Profile (LAEP). Seizures frequency was continuously monitored. Horse welfare was assessed using the Animal Welfare Expertise Protocol (PPBEA). After the TAC intervention, significant improvements were observed in quality of life (p = 0.002), functionality (p < 0.001), adverse effects of medications (p = 0.034) and subjective sleep quality (p = 0.041). In the frequency of crises, there was a significant reduction between 24 weeks (number of episodes: 0; p < 0.001) and 36 weeks (number of episodes: 0.2/person; p = 0.002), indicating a potential period of improvement in crises epileptic. The PPBEA indicated satisfactory welfare conditions for the horses. These findings suggest that CT, through contact with the animal and the three-dimensional movement generated by it, is a promising therapeutic intervention to improve quality of life, functionality, control of adverse effects from the use of medications, quality of sleep and the frequency of epileptic seizures in people with epilepsy.